Aproveitamento da fibra de caju (Anacardium occidentale L.) na formulação de um produto tipo hambúrguer - Galvão, Ana Maria Pinheiro (2006)
The fruits develop fundamental paper on diet and show important characteristics to human nutrition. In Brazil, the productivity of cashew tree is expressive in northeast area where agrobusiness about their subproducts have characterized the throw of many products in segmental industry, in micro and small farmer of the cashew’s culture. Quality’s standard very common for the products produced that guarantee the competivity, establishing solid methodologies that possibity the characterization and the standardization about new products that will be trade in a food standard. Following this tendency, this work needs to develop and to optimize the formulations about one product like hamburguer in base cashew pedunculum (fiber) after this it’s interesting to separate the juice from the basic meat by liquidification, evaluating chemistry, physicochemical, microbiological and sensorial aspects. In this work, was formulated and elaborated three formulations of cashew’s hamburguer in the shapes of roast and raw was submitted to a sensorial analyzes. After this, it was selected only the formulations of samples hamburguers of roast cashew. To conclude that cashew’s hamburguer roast and raw show an appropriate chemistry and microbiological stability and formulation F 1 of sample roast cashew’s hamburguer showed good taste by the part of the consumers being very feasible this elaboration.